RE-DESIGN KEMASAN PRODUK KACANG ATOM GDR DI NAGARI PANYALAIAN, KECAMATAN X KOTO, KABUPATEN TANAH DATAR - ILHAM SYUKRI, Dr. Budiwirman, M.Pd. San Ahdi, M.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
One of the pillars of national economic development is the expansion of small and medium industries. With the presence of a home industry that aims to promote the increase of the National Peanut Enterprises Atom "GDR". Peanuts Enterprises Atom "GDR" is located in Nagari Panyalaian, X Koto subdistrict,district of Tanah Datar, West Sumatera, was established since 1992 under the leadership of Mr. Kemrizal. Peanut Products Atom "GDR" is made from beans that have a large selection taste of tasty and crunchy, it is just that product still has a weakness in the packaging and competitiveness on the national scene. Peanut Products Atom "GDR" is still wearing clear plastic packaging form only and can not compete with other atoms peanut products nationwide.This thesis have a purpose to produce an attractive plan of the design of the product packaging Peanut Atom "GDR" is. The author here wearing design methods started from collecting information with observation, interviews, then more continued by using the method of data analysis using SWOT analysis (Strength, Weakness, Oppoturnity, Treatment), then the author began a creative design. In designing of the packaging design will feature layout, typography, illustration and attractive colors that match the product Peanuts Atom "GDR".Attractive packaging designs will be the main attraction for the consumer to try the Peanut Atom "GDR" in order to upgrade sales and improve national competitiveness.Keywords : Packaging Design, Product, Peanuts Atom "GDR".